Analisis Kinerja Pemerintah Daerah Berdasarkan Informasi Finansial Dan Informasi Non-Finansial Pada Kota Solok (Studi Empiris Pada Pemerintah Daerah Kota Solok Tahun 2014-2016) - Kristy Harly; Mayar Afriyenti (Wahana Riset Akuntansi, 2017)
The good performance of the local government can be seen from the level of community welfare that increases from year to year, but the conditions found in reality show a declining performance but the welfare of society continues to increase. This led to the blurring of government performance in the eyes of society. Because of it, This research was conducted to analyze the performance of local government from two perspectives that is about financial information and non financial information to see whether or not the performance of government. This type of research is qualitative with population and research sample refers to social situations that include places, actors and activities around local taxes and levies. Data obtained by spreading questionnaries and conducting interviews to respondents. The data analysis technique used refers to the value for money and the effectiveness level of the respondent's answer. As a result financially the performance of the local government of Solok is very good but in terms of non-financial, government performance in the eyes of society still have not received a good appreciation for the lack of effectiveness of the implementation of governmentKeyword: financial, non financial, performance, government